The PRIME model: a management solution in academic medicine - Gert J. van Zyl; Maria Nel (South African Family Practice)
Background: The Health Sector and the rendering of health services in South Africa have undergone substantial adjustment since the political change in 1994, filtering through to academic medicine. The managerial responsibilities of the Heads of Department at Medical Schools multiplied. In order to improve their management skills; decrease their frustration; and optimally utilize the highly skilled person-power available, this study endeavoured to establish a management model for use by experienced as well as new Heads of Department in a School of Medicine, measured against the background of good management practices.